Methods of Almsgivinggiving Movement in Kalisapu community by Kawit An-Nur International Boarding School - Imam Tazali; Mohammad Amas Lahat; Amar Ma'ruf; Puspa Fortuna Zulfa; Maksum Maksum; Ellya Verawati (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2023)
Almsgiving is a teaching of Islam, which when done will be rewarded, even Allah SWT promises to increase His favor. However, the phenomenon seen in the Kalisapu community, they still think that by issuing zakat, the wealth will decrease and run out. Therefore, Pondok Modern International Boarding School has a role in providing an understanding of Islamic Education, especially in giving almsgiving. The purpose of this study was to provide an understanding of the application of the almsgiving method to the people of Kalisapu Slawi Tegal. This research uses a qualitative approach. By interviewing respondents. The results of the study provide findings that the application of the almsgiving method is able to stimulate the community to have a sense of humanitarian concern for others actively. With this, the community consciously and unconsciously has been sensitive to the state of the environment by increasing the attitude of generosity and actively participating in religious activities.